Grain Yield and Yield Attributes of Currently Popular Hybrid Rice Varieties Compared to Representative Super Hybrid Rice Varieties in Subtropical Environments - Chengjing Liao; Shengliang Fang; Hengdong Zhang; Longsheng Liu; Jiaxin Xie; Xing Li; Fangbo Cao; Jiana Chen; Min Huang (Agronomy, 2024)
Understanding the yield attributes of the popular rice (Oryza sativa L.) hybrids can provide useful information for developing new hybrid rice varieties. Field experiments were conducted at two subtropical sites (Hengyang and Xingyi) in two years (2021 and 2022) to compare grain yield and yield attributes of three currently popular hybrid rice varieties (Jingliangyouhuazhan, Jingliangyou 534, and Longliangyouhuazhan) with three representative super hybrid rice varieties (Y-liangyou 1, Y-liangyou 2, and Y-liangyou 900). No significant differences in grain yield were observed between the group of popular hybrids and the group of super hybrids at Hengyang and Xingyi in 2021 or at Xingyi in 2022, but at Hengyang in 2022, the group of popular hybrids produced a 15% higher grain yield. The grain yield at Hengyang in 2022 was lower than that at Hengyang and Xingyi in 2021 and at Xingyi in 2022. At Hengyang in 2022, the group of popular hybrids had 9–15% higher panicles per m2, spikelet filling percentage, and harvest index but similar spikelets per panicle and total biomass production and 12% lower grain weight compared to the group of super hybrids. Correlation plot analysis showed that grain yield was significantly related to panicles per m2 but not other yield attributes across six varieties at Hengyang in 2022. These results indicated that the currently popular hybrid rice varieties had higher yield performance than the representative super hybrid rice varieties under the condition of relatively lower productivity, and the key factor for this higher yield performance in the popular hybrids was the higher panicles per m2. This finding highlights that more attention should focus on the yield performance under medium- and low-productivity conditions in hybrid rice breeding programs, and an effective breeding strategy is to select the varieties with high panicle numbers.